KEADILAN HUKUM DALAM MEMPERTIMBANGKAN POST TRAUMATIC SYNDROME DISORDER PADA PENJATUHAN PIDANA DALAM PENGADILAN TINGGI NOMOR 9/Pid.Sus-Anak//2020/PT DKI - Syarah Alfiatin (Jurnal Hukum Adigama, 2021)
As the law state, Indonesia has the purpose of protecting the entire Indonesian nation and all Indonesian bloodshed. It is clearly stated in the constitution of the republic of Indonesia that those who face legal issues, especially children, must get their fundamental rights while serving a sentence. In imposing criminal sanctions on children also, the judge must pay attention to children’s needs and rights. Besides, parents and state social workers must have a role ensuring the protection of the children. It becomes more crucial when the children have a mental disorder and must get continuous treatment as stipulated by law. In the children’s perspective, beyond the fact that whether the children act as perpetrators or victims, the children are still the victim. They can be the victim of parental neglect, misleading parenting, and even the lack of parental supervision. All these situations lead the children to commit law – violating acts. Children with Post Traumatic Syndrome Disorder must get a sense of security either from both parents or the state. The children must get social rehabilitation as special treatment until they recover from their mental disorder.